Tumoral Calcinosis and Epidural Lipomatosis of the Lumbar Spine - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2011)
Lumbar spinal tumoral calcinosis and spinal epidural lipomatosis are rare conditions. We present a 70-year-old female patient with serology negative spondyloarthropathy who developed paresis due to tumoral calcinosis in the left facet joint between L5 and S1 levels and spinal epidural lipomatosis at L5 and Si levels. Surgery was performed to excise the lesions en bloc. Neural decompression was provided. Neurological symptoms improved after surgery. Here, we report the first serology negative spondyloarthropathy case that had concomitant development of tumoral calcinosis and spinal epidural lipomatosis.
Keywords: Tumoral calcinosis; Spinal epidural lipomatosis; Serology negative spondyloarthropathy; Radiculopathy; SYSTEMIC-SCLEROSIS; SCLERODERMA; PATIENT